2003
DOI: 10.1016/s0378-1097(03)00592-5
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence of two different glutamate dehydrogenase activities in the halophilic bacteriumSalinibacter ruber

Abstract: Salinibacter ruber, an extremely halophilic member of the domain Bacteria, has two different cytoplasmic glutamate dehydrogenase activities, marked as GDHI and GDHII. GDHI showed a strong dependence on high salt concentrations for stability, but not for activity, displaying maximal activity in the absence of salts. GDHII depended on high salt concentrations for both activity and stability. It catalyzed amination of 2-oxoglutarate with optimal activity in 3 M KCl at pH 8. No activating effect was found when NaC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
23
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 23 publications
1
23
0
Order By: Relevance
“…Interestingly, no inhibitory effect of isophthalate was observed with NAD-GDH from the three strains (Table 1); this is in contrast to bovine NAD-GDH, which is susceptible to inhibition by isophthalate, terephthalate and phthalate (Caughey et al, 1957). The activity of GDH has been reported to be modulated (activation or deactivation) by nucleotides such as ATP, ADP, AMP and GTP (Bonete et al, 2003;LeJohn & Jackson, 1968;Smith et al, 2001Smith et al, , 2002. However, no such modulatory effect was observed with NADP-GDH from the three strains in this study (data not shown).…”
Section: Discussionmentioning
confidence: 47%
See 3 more Smart Citations
“…Interestingly, no inhibitory effect of isophthalate was observed with NAD-GDH from the three strains (Table 1); this is in contrast to bovine NAD-GDH, which is susceptible to inhibition by isophthalate, terephthalate and phthalate (Caughey et al, 1957). The activity of GDH has been reported to be modulated (activation or deactivation) by nucleotides such as ATP, ADP, AMP and GTP (Bonete et al, 2003;LeJohn & Jackson, 1968;Smith et al, 2001Smith et al, , 2002. However, no such modulatory effect was observed with NADP-GDH from the three strains in this study (data not shown).…”
Section: Discussionmentioning
confidence: 47%
“…The induction of NAD-, NADP-or NAD(P)-GDH has also been reported under varying environmental conditions such as salt (Bonete et al, 1990(Bonete et al, , 2003, temperature (Camardella et al, 2002) and nitrogen source (Abrahams & Abratt, 1998;Brown et al, 1973;LeJohn & McCrea, 1968). In Neisseria meningitidis, transcriptional analysis has shown carbon source-dependent expression of gdhA, leading to a difference in the growth of the strain (Pagliarulo et al, 2004).…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…The amination reaction was monitored at the optimum pH using HEPES-NaOH buffer (100 mM, pH 8.0) for all three GDHs; the deamination reaction for GDH I and GDH II was monitored using CAPS-NaOH (100 mM, pH 10), while the deamination reaction for GDH P was monitored using glycine-NaOH (100 mM, pH 9.5). To determine the kinetic constants for the amination reaction, various concentrations of either ␣-KG (0.05 to 50 mM), NH 4 Cl (0.1 to 250 mM), or NADPH (0.0025 to 0.5 mM) and fixed concentrations of other components (5 mM ␣-KG, 200 mM NH 4 Cl, and 0.15 mM NADPH) were used. For the deamination reactions, various concentrations of either glutamate (1 to 500 mM) or NADP (0.0025 to 0.5 mM) and fixed concentration of either NADP (0.2 mM) or glutamate (100 mM for GDH I and GDH P and 200 mM for GDH II ) were used.…”
mentioning
confidence: 99%